Risk of childhood wheeze and asthma after respiratory syncytial virus infection in full‐term infants. Issue 1 (23rd October 2019) - Mejias, Asuncion; Wu, Bingcao; Tandon, Neeta; Chow, Wing; Varma, Ram; Franco, Eduardo; Ramilo, Octavio
Abstract: Background: Most studies addressing the association between RSV and recurrent wheezing (RW) and asthma have been conducted in patients at risk for lung morbidity. Data in full‐term infants are limited. Methods: The risk of RW/asthma during the first 5 years of life in full‐term infants hospitalized with RSV during the first year (Y) of life was estimated using 2010‐16 data from three claims databases in USA (Truven MarketScan Commercial Claims and Encounters Database [CCAE], Truven Health MarketScan Multi‐State Medicaid [MDCD], and Optum Clinformatics Extended Data Mart‐Socio‐Economic Status [SES]). Full‐term infants with and without RSV infection and ≥ 2 years of continuous health plan enrollment from birth were included. Incidence rates of RW/asthma, cumulative incidence, adjusted incidence rate ratios (aIRR), and odds ratios (aOR) were calculated. Results: During the 16‐year study, 38, 494 (CCAE), 62 846 (MDCD), and 23 099 (SES) matched infant pairs were included in each cohort. In the CCAE database, RW/asthma incidence/1000 patient‐years (69.7 vs 28.7, aIRR: 2.4 [2.3‐2.5]); cumulative incidence (17.6%‐25.2% vs 5.0%‐11.4%); and aOR (Y2: 4.1 [3.9‐4.4]; Y3: 3.2 [3.0‐3.3]; Y4: 2.9 [2.7‐3.1]; Y5: 2.6 [2.5‐2.9]) were higher in the RSV vs. non‐RSV cohort. Results in the SES insured population were comparable, while cumulative incidence and aIRR were higher in the Medicaid population (MDCD). Conclusion: Although there are limitations in this study, including possible coding errors and missing covariates, we showed that full‐term infants with severe RSV infection during the first year of life, spanning several respiratory seasons and a geographically diverse population, are at significant risk of RW/asthma during childhood. Abstract :